2012
DOI: 10.1258/ebm.2011.011301
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 and extracellular inorganic phosphate activate mitogen-activated protein kinase pathway through fibroblast growth factor 23 contributing to hypertrophy and mineralization in osteoarthritic chondrocytes

Abstract: Hypertrophy and impaired mineralization are two processes closely associated with osteoarthritis (OA). 1,25-dihydroxyvitamin D(3) (1a,25(OH)(2)D(3)) and inorganic phosphate (Pi) are two important factors that are implicated in calcium and phosphate homeostasis of bone metabolism and both can be regulated by the circulating phosphaturic factor fibroblast growth factor 23 (FGF23). The objective of this study was to investigate the role of 1a,25(OH)(2)D(3) and Pi and the molecular mechanism through which they con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 44 publications
(53 reference statements)
2
32
0
Order By: Relevance
“…However, the identity of a phosphate “sensor” in osteocytes that might detect high blood phosphate levels and signal FGF23 induction has remained elusive, but recently phosphate signaling of FGF23 has been shown to be dominant over that of 1,25(OH) 2 D 3 /VDR [47]. Additionally, high phosphate [48], along with PHEX and DMP-1 [49], has been demonstrated to require the FGF23 receptor for regulation of FGF23 gene expression. This implies the existence of a crucial autoregulatory circuit that involves extracellular FGF23 and its cognate receptor on osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the identity of a phosphate “sensor” in osteocytes that might detect high blood phosphate levels and signal FGF23 induction has remained elusive, but recently phosphate signaling of FGF23 has been shown to be dominant over that of 1,25(OH) 2 D 3 /VDR [47]. Additionally, high phosphate [48], along with PHEX and DMP-1 [49], has been demonstrated to require the FGF23 receptor for regulation of FGF23 gene expression. This implies the existence of a crucial autoregulatory circuit that involves extracellular FGF23 and its cognate receptor on osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the cells start to express several proteins involved in endochondral ossification such as type X collagen, Indian hedgehog, annexins, VEGF and collagenase 3 16,17 . Interestingly, FGF23, a critical factor of phosphate homeostasis shown to be involved in endochondral ossification 18 is also produced by both growth plate hypertrophic 19 and OA 20,21 chondrocytes suggesting that it may play a role in the switch of OA chondrocytes towards hypertrophy. Indeed, it has been demonstrated that FGF23 triggers normal human chondrocyte toward a hypertrophic phenotype mainly by the upregulation of RUNX2 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors of some previous studies have reported the relatedness between hypertrophy and the extracellular region of the heart, chondrocytes, and astrocytes [24,25,26,27,28,29,30,31]. In particular, Yang et al [29] concluded that SCUBE3, which is an extracellular protein, may account for the accelerated onset and progression of cardiac hypertrophy.…”
Section: Resultsmentioning
confidence: 99%